Chriolepis prolata, a new species of Atlantic goby (Teleostei: Gobiidae) from the North American continental shelf - Hastings, Philip A.; Findley, Lloyd T. (Zootaxa, 2015)
A new species of seven-spined goby of the genus Chriolepis is described from five specimens collected from the continental shelf of the northeastern Gulf of Mexico and Atlantic Ocean off South Carolina in depths of ca 54 to 110 m. The "Platform Goby", Chriolepis prolata, is distinguishable from all other western Atlantic species currently assigned to the genus Chriolepis and the morphologically similar genus Varicus in having pelvic-fin rays one through four branched, the fifth (innermost) pelvic-fin ray unbranched and relatively long (longer than the second ray to longer than all other pelvic-fin rays); most lateral body scales ctenoid, extending anteriorly in a wedge to a level anterior to the first dorsal-fin insertion or nearly to the pectoral-fin axil, with two or more rows of small cycloid scales extending anteriorly to near the pectoral-fin axil, cycloid scales along the bases of the dorsal and anal fins, and no scales on the belly; and the first two anal-fin pterygiophores inserted anterior to the first haemal spine. It closely resembles C. bilix but differs from that species which has a scaled belly, a shorter fifth pelvic-fin ray, prolonged dorsal-fin spines and smaller teeth in the lower jaw. An earlier report of C. bilix from Florida waters apparently refers to C. prolata.